A descriptive analysis of tax evasion as a crime in a least developed country: the case of Yemen (Journal of Business Management and Accounting, 2011)
This paper measures the perception of Yemeni citizens on the severity of tax evasion relative to other crimes and violations. Perception of tax evasion may somewhat explain the degree of non-compliance with tax laws. Using data from a self-administered survey and a structured interview, the results of mean and comparative analysis show that the three tax evasion offences were ranked as the least serious crimes among 30 listed crimes. Further, tax evasion is categorized the least serious category out of six categories. The results of this study should be useful to policy makers in Yemen and elsewhere, as it is an alarming signal that tax evasion is relatively ranked as the least serious offence, which could lead to an environment where taxpayers may not be afraid of cheating on their tax returns.